Validation of MELD 3.0 and ReMELD-Na scoring systems: a German clinical cohort study - Putri, Aghnia Jolanda; Jiang, Decan; Czigány, Zoltán; Mehrabi, Arianeb; Büchler, Markus W.; Merle, Uta; Michalski, Christoph; Husen, Peri (Langenbeck's archives of surgery, 2025)
The Model for End-Stage Liver Disease (MELD) score, introduced in 2002, has since been refined. MELD 3.0, launched in 2023 in the United States, improves mortality prediction by incorporating sex and albumin. Since March 2025, Germany started to use reMELD-Na to improve prioritization of patients on the waiting list for liver transplantation (LT). This study compares the performance of original MELD, MELD-Na, MELD 3.0 with and without albumin, and reMELD-Na for patients waitlisted for LT in a large German transplant center.